Three-dimensional visualization of heart-wide myocardial architecture and vascular network simultaneously at single-cell resolution - Chen, Jianwei; Liu, Guangcai; Sun, Wen; Zheng, Yuanfang; Jin, Jing; Chen, Siqi; Yuan, Jing; Gong, Hui; Luo, Qingming; Yang, Xiaoquan (Frontiers in Cardiovascular Medicine, 2022)
Obtaining various structures of the entire mature heart at single-cell resolution is highly desired in cardiac studies; however, effective methodologies are still lacking. Here, we propose a pipeline for labeling and imaging myocardial and vascular structures. In this pipeline, the myocardium is counterstained using fluorescent dyes and the cardiovasculature is labeled using transgenic markers. High-definition dual-color fluorescence micro-optical sectioning tomography is used to perform heart-wide tissue imaging, enabling the acquisition of whole-heart data at a voxel resolution of 0.32 × 0.32 × 1 μm3. Obtained structural data demonstrated the superiority of the pipeline. In particular, the three-dimensional morphology and spatial arrangement of reconstructed cardiomyocytes were revealed, and high-resolution vascular data helped determine differences in the features of endothelial cells and complex coiled capillaries. Our pipeline can be used in cardiac studies for examining the structures of the entire heart at the single-cell level.